2019
DOI: 10.24106/kefdergi.2376
|View full text |Cite
|
Sign up to set email alerts
|

Üniversite Öğrencilerinin Siber Aylaklık Seviyelerini Yordayan Faktörler

Abstract: Eğitim ortamlarında siber aylaklık davranışı, öğrenme ve disiplin problemleri oluşturmaktadır. Bu araştırmanın amacı eğitim ortamlarındaki siber aylaklığın yordayıcılarını ve nedenlerini ortaya koymaktır. Bu amaç doğrultusunda, 124 üniversite öğrencisine Siber Aylaklık Davranışları Ölçeği uygulanmış ve bu davranışları neden gösterdikleri sorulmuştur. Öğrencilerin siber aylaklık düzeylerinin yordayıcılarını belirlemek üzere çoklu doğrusal regresyon analizi yapılmıştır. Siber aylaklık davranışlarının nedenine il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 13 publications
1
5
0
1
Order By: Relevance
“…On the other hand, the results with respect to student-based reasons for cyberloafing are to a great extent in line with previous studies (e.g., Bağrıaçık-Yılmaz, 2017;Ergün & Altun, 2012;Şenel et al, 2019;Varol & Yıldırım, 2018;2019). The results show that respondents attached greater importance to their personal problems and affairs, got or felt bored and could not or did not concentrate during online classes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…On the other hand, the results with respect to student-based reasons for cyberloafing are to a great extent in line with previous studies (e.g., Bağrıaçık-Yılmaz, 2017;Ergün & Altun, 2012;Şenel et al, 2019;Varol & Yıldırım, 2018;2019). The results show that respondents attached greater importance to their personal problems and affairs, got or felt bored and could not or did not concentrate during online classes.…”
Section: Discussionsupporting
confidence: 90%
“…Some other researchers (e.g. Knight, 2017;Koay, 2018;Şenel, Günaydın, Sarıtaş, & Çiğdem, 2019), on the other hand, used Akbulut et al's (2016) scale and reported checking posts, checking social networking profiles, sharing content on social networks, liking posts, commenting on shared photos, posting status updates on social networks, tagging friends on photos, chatting, watching shared videos, shopping online, visiting deal-of-the-day websites, visiting online shopping sites, visiting auction sites, using online banking services, visiting online shops for used products, checking job advertisements, downloading music, watching videos online, listening to music online, downloading videos, downloading applications, visiting betting/gambling sites, betting and gambling online, checking online sport sites, playing online games, commenting on trending topics, posting tweets, reading tweets, favouriting a tweet, and retweeting a tweet as types of cyberloafing behaviours students engage with during class hours. In addition to this, there are also studies (e.g., Akgün, 2020;Çok, 2018;Dursun et al, 2018;Sarıtepecı, 2019) that used the same scale and reported its sub-dimensions sharing, shopping, real-time updating, accessing online content, gambling as types of cyberloafing behaviours students carry out.…”
Section: Introductionmentioning
confidence: 99%
“…In the findings, it was found that upperclass students were more prone to cyberloafing compared to lower-class students. Şenel, Günaydın, Sarıtaş, and Çiğdem (2019) examined the level of cyberloafing with 124 university students. It was seen that the students' cyberloafing level was "moderate".…”
Section: Literaturementioning
confidence: 99%
“…(e.g. Çınar and Cinisli, 2018;Çok and Kutlu, 2018;Mercado, Giordano and Dilchert, 2018;Şenel et al, 2019). This may be due to the differences in the scale and scale contents used on cyberloafing behaviors, the differences in the age group of the students, and the differences in the type and number of technological devices they use.…”
Section: Findings On the Cyberloafing Levels Of Middle School Studentsmentioning
confidence: 99%
“…Türkçe literatürde ise araştırmaların genellikle işletme alanında yapıldığı tespit edilmekle birlikte, yeni bir konu olduğu gözlemlenmiştir. Eğitim yönetimi alanında sanal kaytarma ile ilgili çalışmalar (Altun ve Ergün, 2012;Akca, 2013;Özdem ve Demir, 2015;Arık, 2016;Hayıt ve Dönmez, 2016;Demir ve Seferoğlu, 2016;Yılmaz, 2017;Varol ve Yıldırım, 2017;Ataş, 2017;Polat, 2018;Şenel, Günaydın, Sarıtaş ve Çiğdem, 2019)…”
Section: Yönetsel Ve Sanal Kaytarma Davranışıunclassified